Os preceitos da sustentabilidade na gestão empresarial: um estudo correlacional sob o viés da percepção de gestores e colaboradores de empresas da região sudoeste do Paraná - Huppes, Leila Cristina (2014)
Sustainable development, a pressing approach, has changed businesses meaningfully and is based on economic, environmental and social bottom lines. Upon this context, new rules on business competition come up, supported especially by the changes in the standards of consumers’ behavior; demanding the company to adjust to new management paradigms. Sustainability is regarded as strategy for business competition however; the concept seems to be still controversial among researchers, experts and businesspeople. It is also in point of discussion how much managers and employees understand the idea of sustainability and whether companies are overlooking this goal or not. The present dissertation aims to analyze these aspects through an empirical and theoretical study. Its purpose, in a nutshell, is to identify managers’ and employees’ knowledge about corporate sustainability, in four major companies, from both industrial and commercial segments, in Southwest Paraná. The method adopted is quantitative and qualitative; nonparametric statistics were used to compare the answer of all interviewed employees. Managers have also been interviewed and their answers confronted the employees’. The general outcome of the study showed that most individuals in this context have a limited knowledge about the concept of sustainability, worrying more about its financial impacts than the environmental ones. Nevertheless, it was possible to identify diverse actions, social and environment-related, which have been put into practice by the companies. The research determined that the idea of sustainability is clearer among managers, mostly because it is not usually brought to employees and other individuals involved.